(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3GdLGeYi GdOaY hCgd GdQHY cCMOge s
(3BNQgG (B:s
(3hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf hfLR GdLRA GdChd ef GdeYjGQ hGdeZQH hGdLGeY GdeYQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
Keywords: (3Gdabg GdeGdcjs